HOW ARE PLANT SPECIES IN CENTRAL EUROPEAN BEECH (FAGUS SYLVATICA L.) FORESTS AFFECTED BY TEMPERATURE CHANGES? SHIFT OF POTENTIAL SUITABLE HABITATS UNDER GLOBAL WARMING - Jantsch, M. C.; Fischer, H. S.; Winter, S.; Fischer, A. (Annali di Botanica, 2013)
This study reveals which temperature range is favoured or avoided by 156 forest plant species and how the distribution of potential suitable habitats of species in beech forests may change in the future. We performed 140 phytosociological relevés along a temperature gradient (4.1 to 9.8 °C) in Bavaria, southern Germany, on south exposed slopes. One half of the plots were located on acidic substrate, the other half on base-rich substrate. Generalized linear models (GLM) were used to analyse species occurrence along the temperature gradient and to model habitats for species in beech forests under a present (1971-2000) and a future climate (2071-2100) scenario assuming a temperature increase of 1.8 °C. Herb species of beech forests are more adapted to lower temperatures and tree species more to higher temperatures. Current habitats will clearly change under increasing temperatures. We found large habitat losses for Luzula sylvatica (Huds.) Gaudin, Maianthemum bifolium (L.) F. W. Schmidt, Picea abies (L.) H. Karst., Prenanthes purpurea L. and large habitat gains for Carpinus betulus L., Impatiens parviflora DC., Prunus avium (L.) L. and Quercus petraea (Matt.) Liebl. on both substrates. Forestry will be affected positively as well as negatively with a change in tree cultivation. Losses in biodiversity might be strong for mountainous forests and must also be considered in future conservation plans.